سيميائية العتبات النصية في ديواني )ما في الجبة غير البحر ا ولكتابة عمى الشجر( لمشاعر فاتح علاق - زنقي, سماح; وصيف السعيد, شهرزاد; الأعوج, مسعودة (جامعة الوادي - University of Eloued, 2023)
إن لكل نص بناء ولكل بناء جنس ولكل جنس عتبات ولكل عتبة مفتاح للولوج إلى عوالمها، لهذا اهتمت السيميائية الحديثة المعاصرة بدراسة الإطار الذي يحيط بالنص،والمتمثل في العتبات الخارجية من الغلاف واسم المؤلف والعنوان والمؤشر الجنسي والناشر. الفصل الأول: تناول مفاهيم السيميائية والعتبات النصية . الفصل الثاني: دراسة العتبات النصية في ديوانين هما (الكتابة على الشجر وما في الجبّة غير البحر)، من عتبات أمامية وعتبات داخلية وعتبات خلفية. Summary Each text has a structure, and each structure has a gender, and each gender has thresholds, and each threshold has a key to access its worlds. That is why contemporary semiotics focused on studying the framework surrounding the text, which is represented in the outer thresholds of the cover, the name of the author, the title, the sexual indicator, and the publisher. The first chapter deals with the concepts of semiotics and textual thresholds. The second chapter: a study of the textual thresholds in two collections (the writing on the trees and what is in the veil other than the sea), from the front thresholds, the inner thresholds, and the rear threshol
Keywords: لعتبات، المناص، العناوين الداخلية، العنوان الرئيس; text, thresholds, platforms, internal addresses, main address